Colonial shadows – a systematic review of the Xavante health transformation - Katarzyna Górka (International Journal for Equity in Health)
Abstract Background From a biocultural perspective, health is a multifaceted concept shaped not only by biomedical factors but also by social, cultural, political, and economic forces. In Indigenous contexts, health is particularly vulnerable, as it is profoundly influenced by external socioeconomic and cultural changes, often introduced or imposed by the broader society. The Xavante Indigenous community, located in the Central-Western region of Brazil, is one of the most extensively studied Indigenous groups in the country in terms of health. Despite a rich body of literature addressing various aspects of their health, there has been a notable absence of comprehensive studies that trace the historical evolution of their health status through bibliographic analysis. This article seeks to fill this gap by providing an in-depth examination of the historical transformation of the Xavante health, positioning this issue within the broader discourse of Indigenous health as a public health concern, while applying a decolonial perspective. Methods A systematic bibliographic analysis was conducted to trace the historical trajectory of health among the Xavante people from Mato Grosso, Brazil. Results A total of 109 academic publications meeting the inclusion criteria were identified. The analysis revealed sustained scholarly interest in the health of the Xavante community, particularly since their first sustained contact with the urbanized society. A comparative examination of the earliest and most recent, comprehensive studies on this topic highlighted a marked decline in the health status of the Xavante people over time. Conclusions Despite periodic shifts in the administrative frameworks governing Indigenous healthcare in Brazil, including reductions in mortality rates and increased utilization of hospital services, the overall health status of the Xavante has significantly deteriorated. This article critically analyzes this trend through a decolonial lens, highlighting the limitations and shortcomings of existing health policies and interventions. It argues that the prevailing colonial approach to healthcare, compounded by the denial of culturally appropriate services, represents a clear violation of human rights. Furthermore, the article underscores the substantial impact of social determinants—such as historical trauma, cultural disruption, and systemic inequality—on the health outcomes of this community.